Efektivitas Kombinasi Pijat Oksitosin dan Woolwich Massage Serta Breastcare terhadap Peningkatan Produksi Asi pada Ibu Menyusui di Klinik Dr Fitri Khairani Pulungan - Jamilah, Jamilah; Yunaesah, Yunaesah (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Breast milk production is influenced by physical and psychological factors of breastfeeding mothers. If these two factors are not met then breast milk production will not run smoothly.   Physical factors, especially regarding adequate, balanced and healthy maternal nutritional intake, as well as maternal health factors. Psychological factors consist of feeling comfortable, calm and positive thinking.  As well as support from those closest to you such as your husband and family. This makes researchers consider the importance of having a strategy that is a solution to all obstacles to exclusive breastfeeding. Oxytocin massage therapy and Woolwich massage are carried out at the Jagakarsa District Health Center to increase breast milk production and provide comfort to breastfeeding mothers. Oxytocin massage is massage along the spine (vertebrae) up to the fifth and sixth rib bones and is an attempt to stimulate the hormones prolactin and oxytocin after giving birth.To determine the effectiveness of the combination of oxytocin massage, Woolwich massage and breast care in increasing breast milk production in breastfeeding mothers at the Dr. Fitri Khairani Pulungan clinic.The type of research used is quantitative research with an observational analytical research design, using a cross sectional research approach. Sampling was carried out using a saturated sampling technique totaling 20 people. Data techniques include univariate analysis using frequency distribution and bivariate analysis using statistical calculations from the SPSS program. The results of this study showed an increase in breast milk production in breastfeeding mothers in the control group with the statistical data results of the Wilcoxon pvalue test being 0.000 because the value of 0.000 was smaller than 0.05 (0.000 < 0.05), so it was concluded that Ha was accepted. H0 was rejected.The difference in the effectiveness of oxytocin massage and Woolwich massage with breast care, both techniques used for breastfeeding mothers have the same effectiveness in that they can influence the oxytocin reflex and increase the hormone prolactin which affects breast milk production Keywords: Oxytocin Massage, Woolwich Massage, Breastcare Increase Breast Milk Production ABSTRAK Produksi ASI dipengaruhi oleh faktor fisik dan psikologis ibu menyusui. Bila ke dua faktor tersebut tidak terpenuhi maka produksi   ASI   tidak   lancar.   Faktor   fisik   terutama   mengenai   asupan  gizi   ibu   yang mencukupi, seimbang dan sehat, serta faktor kesehatan ibu. Faktor psikologis terdiri dari rasa  nyaman,  tenang  dan  berfikiran  positif.  Serta  dukungan  dari  orang  terdekat  seperti suami dan keluarga. Hal ini membuat peneliti menganggap ungensi, perlu adanya   strategi   yang   menjadi   solusi   darisegala   kendala   pemberian   ASI   eksklusif. Untuk mengetahui Efektivitas Kombinasi Pijat Oksitosin Dan Woolwich Massage Serta Breastcare Terhadap Peningkatan Produksi Asi Pada Ibu Menyusui Pada Klinik dr fitri khairani pulungan. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan desain penelitian analitik observasional, dengan menggunakan pendekatan penelitian cross sectional. Pengambilan sampel dilakukan dengan cara teknik sampling jenuh berjumlah 20 orang. Teknik data termasuk dalam analisis univariat menggunakan distribusi frekuensi dan analisis bivariat menggunakan perhitungan statistik program SPSS. Hasil dari penelitian ini Terdapat  Peningkatan  produksi  ASI  pada  ibu  menyusui  pada  kelompok  control dengan hasil data statistik Uji Wilcoxon pvalue bernilai 0,000 karena nilai 0.000 lebih kecil dari 0,05 (0.000 < 0.05) maka disimpulkan bahwa Ha diterima H0 ditolak.. Perbedaan  efektivitas  pijat  oksitosin  dan  woolwich  massage  dengan  breast  care, kedua  teknik  yang  dipakai  untuk  ibu  menyusui  mempunyai  efektivitas  yang sama dimana dapat mempengaruhi reflex oksitosin dan meningkatkan hormone prolactin yang mempengaruhi produksi ASI. Kata Kunci: Pijat Oksitosin, Woolwich Massage, Breastcare Peningkatan Produksi Asi